Effectiveness of Collaborative and Individualized Learning on the Learners’ Achievement in Science Among Pupils - Almonia, Acil L. (Integrated Science Education Journal, 2024)
Purpose of the study: As the Philippine educational system transitions back to face-to-face classes post-pandemic, there are significant challenges, particularly in primary education. This study examines the effectiveness of collaborative versus individualized learning in students' achievement in science. The research focuses on fifty (50) grade 5 pupils from a public elementary school in Gingoog City during the SY 2022-2023. Methodology: The study utilized an experimental research design. Two groups of students were given both pretests and posttests. Data analysis was performed using percentages and t-tests to determine the effectiveness of each learning approach. Main Findings: The results revealed a notable difference in pretest scores between pupils engaged in Collaborative Learning and those in Individualized Learning. Posttest scores also showed a significant improvement in pupils exposed to Collaborative Learning compared to Individualized Learning. The t-test results confirmed significant differences in both pretest and post-test scores within each group, emphasizing the superior impact of Collaborative Learning on student performance. Novelty/Originality of this study: This study highlights the transformative potential of Collaborative Learning in the context of post-pandemic education. Collaborative Learning significantly enhances students' academic performance in Science by fostering interaction and cooperative problem-solving. The research suggests that the daily implementation of Collaborative Learning can be a powerful tool for improving educational outcomes. Furthermore, the study opens avenues for applying Collaborative Learning strategies across other subjects such as Filipino, English, Araling Panlipunan, and Mathematics, potentially revolutionizing pedagogical approaches in primary education in the Philippines.